Downscaling screening cultures in a multifunctional bioreactor array‐on‐a‐chip for speeding up optimization of yeast‐based lactic acid bioproduction. Issue 7 (6th April 2020) - Totaro, Damiano; Rothbauer, Mario; Steiger, Matthias G.; Mayr, Torsten; Wang, Hsiang‐Yu; Lin, Yu‐Sheng; Sauer, Michael; Altvater, Martin; Ertl, Peter; Mattanovich, Diethard
Abstract: A key challenge for bioprocess engineering is the identification of the optimum process conditions for the production of biochemical and biopharmaceutical compounds using prokaryotic as well as eukaryotic cell factories. Shake flasks and bench‐scale bioreactor systems are still the golden standard in the early stage of bioprocess development, though they are known to be expensive, time‐consuming, and labor‐intensive as well as lacking the throughput for efficient production optimizations. To bridge the technological gap between bioprocess optimization and upscaling, we have developed a microfluidic bioreactor array to reduce time and costs, and to increase throughput compared with traditional lab‐scale culture strategies. We present a multifunctional microfluidic device containing 12 individual bioreactors ( V t = 15 µl) in a 26 mm × 76 mm area with in‐line biosensing of dissolved oxygen and biomass concentration. Following initial device characterization, the bioreactor lab‐on‐a‐chip was used in a proof‐of‐principle study to identify the most productive cell line for lactic acid production out of two engineered yeast strains, evaluating whether it could reduce the time needed for collecting meaningful data compared with shake flasks cultures. Results of the study showed significant difference in the strains' productivity within 3 hr of operation exhibiting a 4‐ to 6‐fold higher lactic acid production, thus pointing at the potential of microfluidic technology as effective screening tool for fast and parallelizable industrial bioprocess development. Abstract : The authors developed a microfluidic platform with integrated in‐line oxygen and biomass sensors capable of performing perfusion cultures, which was tested for the screening of engineered lactic acid overproducing S. cerevisiae strains. On‐chip cultures enabled the identification of the best producer and they were validated by a comparative study with shake flask cultures. The microfluidic platform could provide data about strain performance 6 to 7 times faster, thanks to a lower amount of biomass required and higher throughput.